Archeometric study of pottery shards from Conjunto Vilas and São João, Amazon. (February 2020) - Oliveira, L.S.S.; Abreu, C.M.; Ferreira, F.C.L.; Lopes, R.C.A.; Almeida, F.O.; Tamanaha, E.K.; Belletti, J.S.; Machado, R.; Rizzutto, M.A.; Souza, D.N.
Abstract: In this work, we investigated through archeometry studies the mineralogical composition of pottery shards from Conjunto Villas and São João archeological sites located in the macro-region of middle Solimões, in the State of Amazonas, Brazil. Archeometric analyses are fundamental for classification and characterization of ancient ceramics, providing relevant data that can furnish information about production processes, types of use and social meaning of these materials. The shards were studied by optical microscopy (OM), Fourier transform infrared (FTIR) spectroscopy, energy dispersive x-ray fluorescence (ED-XRF), X-ray diffraction (XRD), and scanning electron microscopy, coupled with energy-dispersive X-ray analysis (SEM-EDX). Al, Si, K, Ca, Ti and Fe (as oxides) were identified among other minority elements in the ceramic pastes, besides the presence of cauixi and caraipé (non-plastic materials), as well as possibly shells. The crystalline phases identified were quartz, hematite, kaolinite, anatase, dolomite and illite-muscovite, being that the kaolinite was found more frequently in ceramics. The results obtained in this work add important information about the analyzed artifacts, allowing a better understanding of the ancient civilizations from the Amazon region. Highlights: Studies on pottery shards from archeological sites were performed. The shards were studied by FTIR, XRD, ED-XRF, and SEM-EDX. Kaolinite was the crystalline phases found more frequently in ceramics. The shards have silicon-based non-plastic materials between their constituents.